Novel technique for visualizing primordial germ cells in sturgeons (Acipenser ruthenus, A. gueldenstaedtii, A. baerii, and Huso huso) - Saito, Taiju; Psenicka, Martin (Biology of reproduction, 2015)
Primordial germ cells (PGCs) are the origin of all germ cells in developing embryos. In the sturgeon embryo, PGCs develop from the vegetal hemisphere, which mainly acts as an extraembryonic source of nutrition. Current methods for studying sturgeon PGCs require either killing the fish or using costly and time-consuming histological procedures. Here, we demonstrate that visualization of sterlet (Acipenser ruthenus>) PGCs in vivo is feasible by simply labeling the vegetal hemisphere with fluorescein isothiocyanate (FITC)-dextran. We injected FITC-dextrans, with molecular weights varying between 10 000 and 2 000 000, into the vegetal pole of 1- to 4-cell stage embryos. At the neurula to tail-bud developmental stages, FITC-positive PGC-like cells appeared ventrally around the developing tail bud in the experimental group that received a high-molecular-weight FITC-dextran. The highest average number of FITC-positive PGC-like cells was observed in embryos injected with FITC-dextran having a molecular weight of 500 000 (FD-500). The pattern of migration of the labeled cells was identical to that of PGCs, clearly indicating that the FITC-positive PGC-like cells were PGCs. Labeled vegetal cells, except for the PGCs, were digested and excreted before the embryos starting feeding. FITC-labeled PGCs were observed in the developing gonads of fish for at least 3 mo after injection. We also found that FD-500 could be used to visualize PGCs in other sturgeon species. To the best of our knowledge, this report is the first to demonstrate in any animal species that PGCs can be visualized in vivo for a long period by the injection of a simple reagent.
Keywords: Germ Cells; embryo nesavčí; sturgeon; Embryo, Nonmammalian; embryonální vývoj; ryby; molekulová hmotnost; fluorescein-5-isothiokyanát; Dextrans; mikroinjekce; Female; developmental biology; bičík spermie; zvířata; primordial germ cells; Embryonic Development; Fishes; fluorescenční barviva; ženské pohlaví; pohyb buněk; Fluorescent Dyes; Male; gonad development; early development; Cell Movement; Microinjections; Fluorescein-5-isothiocyanate; Animals; dextrany; mužské pohlaví; fish reproduction; zárodečné buňky; Sperm Tail; Molecular Weight